The fourth power mean of the generalized quadratic Gauss sums associated with some Dirichlet characters - Wang, Xuan; Wang, Li; Chen, Guohui (AIMS mathematics, 2024)
In this paper, the fourth power mean values of the generalized quadratic Gauss sums associated with the $ 3 $-order and $ 4 $-order Dirichlet characters are given by using the properties of the Dirichlet characters and Gauss sums.